Prediction model for behavioral intention to use E-HRM through awareness in Jordanian five-star hotels - Alsheikh, Ghaith Abdulraheem Ali; Al-Ghalabi, Ruba Risheed; Altarawneh, Abeer; Al-Shamaileh, Laith R. (Heritage and Sustainable Development, 2024)
Using web-based technologies in various HR procedures is the concept of Electronic Human Resource Management or E-HRM. It makes a big difference to the efficiency of the business by providing several options for getting things done quickly. Nevertheless, there has been scant investigation into this field, and its maximum potential remains untapped, despite its meteoric rise. The present research also suggests adding the Technology Acceptance Model (TAM) to the E-HRM continuity model to find out what factors affect workers' behavioral intention to use E-HRM systems, and how awareness plays a role in this. In order to help advance E-HRM as a field, this study aims to expand the theoretical bounds of existing research. 400 prospective employees were scouted from Jordanian five-star hotels as part of the convenience sampling procedure used to get the data. Starting in January 2022, the data was collected over one month. We used a Structural Equation Model (SEM) with Smart PLS on the dataset to evaluate our hypothesis. The study found that behavioral intention to use E-HRM is significantly influenced by perceived usefulness, perceived ease of use, trust, and subjective norms. The results only backed up two of the four hypotheses on the moderator effect. Hotel workers will be better able to handle high levels of stress and conduct their jobs more efficiently if the industry adopts E-HRM technology.